KECEMASAN BERBICARA DITINJAU DARI KONSEP DIRI DAN KECERDASAN EMOSIONAL - Kholisin Kholisin (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2014)
This study aims to test empirically the effect of self-concept of the anxiety of public speaking, the influence of emotional intelligence to the anxiety of public speaking, and the influence of self-concept and emotional intelligence to the anxiety of public speaking. Subjects were students of KKN force 64th 2015 Faculty of Da'wa and Communication UIN Walisongo Semarang in Waterford District are obtained using cluster random sampling. Data were analyzed using linear regression analysis simple and multiple linear regression. Moreover, the multiple linear regression analysis was used to test the effect of self-concept and emotional intelligence simultaneously to the anxiety of public speaking. The results showed: 1). Self-concept significantly influence the anxiety of public speaking, amounting to 51.9%. 2). Emotional intelligence significantly influence the anxiety of public speaking, amounting to 34.9%. 3). The concept of self and emotional intelligence influence simultaneously to the anxiety of public speaking, amounting to 60.4%.*** Penelitian ini merupakan penelitian kuantitatif yang bertujuan untuk menguji secara empiris pengaruh konsep diri terhadap kecemasan berbicara di depan umum, pengaruh kecerdasan emosional terhadap kecemasan berbicara di depan umum, dan pengaruh konsep diri dan kecerdasan emosional terhadap kecemasan berbicara di depan umum. Subyek penelitian adalah mahasiswa KKN angkatan ke-64 tahun 2015 Fakultas Dakwah dan Komunikasi UIN Walisongo Semarang di Kabupaten Temanggung secara cluster random ampling. Teknik analisis data menggunakan analisis regresi linier sederhana dan regresi linier berganda. Hasil penelitian ini menunjukkan: 1). Konsep diri berpengaruh secara signifikan terhadap kecemasan berbicara di depan umum, yaitu sebesar 51,9%. 2). Kecerdasan emosional berpengaruh secara signifikan terhadap kecemasan berbicara di depan umum, yaitu sebesar 34,9%. 3). Konsep diri dan kecerdasan emosional berpengaruh secara simultan terhadap kecemasan berbicara di depan umum, yaitu sebesar 60,4%.